Knowledge and Practice of Pesticides among the Farmer of Bhaktapur Municipality, Nepal - Humagain, Nisha (Health Prospect, 2024)
Background and Objectives: Pesticides are the substances that are used in agriculture to prevent, destroy and control unwanted pests, weeds, and other plant diseases to enhance the production, processing, storage, and transport of food and agriculture commodities. The use of pesticides dramatically increases agricultural production and productivity. However, there are some negative externalities from such use of pesticides, as the use of pesticides raises the negative impact also increases. So, the objective of this study is to assess the knowledge and practice of pesticide use among farmers of Bhaktapur municipality Methods: A self-designed questionnaire about knowledge and practice of pesticide use was distributed to the farmers of Bhaktapur municipality. The questionnaires were collected, processed, analyzed, and tabulated to find out the existing knowledge and practices of farmers about pesticides use. Results: This study comprised 54.1% (n=106) females and 45.9 %( n=90) males in the suburb of Bhaktapur. The majority of the pesticide users were aware of the environmental impacts of pesticides. 40.8% were stored in dedicated pesticide stores and 69.4% of the respondents got information about using pesticides from the salesman. However, only 58.2% of the respondents take into account the preventive measure of Acute Pesticides Poisoning (APP). Conclusion: Despite having adequate knowledge of pesticide use, farmers seem to be less aware of the hazard of pesticides. Certain efforts must be placed not only to provide additional knowledge on the risks of pesticide use but also on the execution of Personal Protective Measures (PPM) which is also necessary to decrease the pesticide exposure of farmworkers. Various awareness programs and easy provisions/ supply of PPE would significantly reduce the risk of pesticides.